2019
DOI: 10.1128/jcm.01351-19
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Dispersal Patterns of Hypervirulent Meningococcal Strains of Serogroup C:cc11 by Phylogenomic Time Trees

Abstract: Neisseria meningitidis is one of the few commensal bacteria that can even cause large epidemics of invasive meningococcal disease (IMD). N. meningitis serogroup C belonging to the hypervirulent clonal complex 11 (cc11) represents an important public health threat worldwide. We reconstructed the dispersal patterns of hypervirulent meningococcal strains of serogroup C:cc11 by phylogenomic time trees. In particular, we focused the attention on the epidemic dynamics of C:P1.5.1,10-8:F3-6;ST-11(cc11) meningococci c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The study suggested a possible first introduction in our country between 2007 and 2011, where this variant was spreading among several European countries ( Lo Presti et al, 2019 ). The second possible introduction could be reconducted between 2013 and 2014 ( Lo Presti et al, 2019 ). It is likely that this strain has spread in Italy and remains stable as suggested by genomic and phylogenetic analysis, here reported.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The study suggested a possible first introduction in our country between 2007 and 2011, where this variant was spreading among several European countries ( Lo Presti et al, 2019 ). The second possible introduction could be reconducted between 2013 and 2014 ( Lo Presti et al, 2019 ). It is likely that this strain has spread in Italy and remains stable as suggested by genomic and phylogenetic analysis, here reported.…”
Section: Discussionmentioning
confidence: 84%
“…Based on our previously study on MenC strains circulating in Italy ( Lo Presti et al, 2019 ), using a Bayesian method to reconstruct the epidemiological dynamics, the C:P1.5-1,10-8:F3-6:ST-11(cc11) genotype segregated into two distinct clades, both apparently originating from UK, but in a different time periods. The study suggested a possible first introduction in our country between 2007 and 2011, where this variant was spreading among several European countries ( Lo Presti et al, 2019 ). The second possible introduction could be reconducted between 2013 and 2014 ( Lo Presti et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…the predominance of the hypervirulent clonal complex cc11 in MenC isolates from IMD, has been observed in a number of studies [31][32][33]. Phylogenetic analyses have shown that the hypervirulent strain C, cc11 (UK-strain) has spread in a number of European countries [34]. A study from the Republic of Ireland over a 19-year period (1996-2015) also demonstrated the homogeneity of MenC isolates from IMD, with a prevalence of cc8 and cc11 [30].…”
Section: Plos Onementioning
confidence: 86%
“…As for N. meningitidis, there was a low incidence of invasive meningococcal diseases in Italy in 2017-2019, fluctuating around 0.3 cases/100,000 inhabitants, which may have led to a decrease in the attention of the public. Anyway, outbreaks due to N. meningitidis serogroup C occurred in Central and North Italy during 2015-2016 and 2019-2020, respectively [17,18].…”
Section: Discussionmentioning
confidence: 99%